Impact of primary market on total factor productivity: A cross-country analysis - Vinod Kumar; Ganesh Kumar Nidugala (Cogent Economics & Finance, 2020)
Schumpeter argued that entrepreneurial finance causes the absorption of innovation in the economy and productivity growth. Previous empirical work, however, reported an insignificant relationship between the primary equity market and economic growth, and suggested exploration of the routes through which the primary equity market may affect economic growth. In the present study, we examined the impact of the primary equity market on total factor productivity (TFP) and non-TFP growth in a cross-country setting using panel data analysis and the GMM approach. We employed published data relating to 87 countries for the period 1990-2014. We found a positive impact of the primary equity market on TFP in both developed and developing economies, without a significant difference. The impact of the primary equity market on non-TFP growth was found to be significant in developing economies only. The findings suggest that the primary equity market boosts growth in all economies, but the impact is higher in developing economies. Findings of the study suggest that policy makers should focus on developing primary equity market to foster economic growth.
Keywords: 330; economic growth; Mckinnon model; primary equity market; Schumpeter model; total factor productivity